Noninvasive Positive-Pressure Ventilation for Preeclampsia-Induced Pulmonary Edema: 3 Case Reports and a Literature Review - Kohei Hamada; Yoshitsugu Chigusa; Eiji Kondoh; Yusuke Ueda; Shunsuke Kawahara; Haruta Mogami; Akihito Horie; Tsukasa Baba; Masaki Mandai (Hindawi Limited, 2018)
Pulmonary edema caused by severe preeclampsia can be an indication for pregnancy termination. We aimed to investigate whether noninvasive positive-pressure ventilation (NPPV) was useful for preeclampsia-induced pulmonary edema. Three cases of preeclampsia-induced pulmonary edema managed with NPPV in our institute were reviewed retrospectively. A literature review was conducted regarding NPPV usage during pregnancy. NPPV was initiated at 30, 20, and 24 weeks of gestation in the 3 cases. In all cases, NPPV slowed the progression of pulmonary edema and succeeded in delaying pregnancy termination by 17 days on average. Maternal outcomes were positive, and no intubation was required. Between 1994 and 2017, there were 11 articles describing 12 cases in which NPPV was applied for pulmonary edema during pregnancy. However, there has been no case of NPPV management of preeclampsia-induced pulmonary edema thus far. Maternal and fetal outcomes were positive in these 12 cases. NPPV may contribute to prolonging pregnancy in patients with poor oxygenation due to preeclampsia-induced pulmonary edema. However, patients should be closely monitored, and the decision to intubate or terminate the pregnancy should be made without delay when the maternal or fetal condition worsens.